PERSEPSI WISATAWAN TERHADAP WISATA SPIRITUAL MELUKAT DI TAMAN BEJI SAMUAN, BALI - Ekasani, Kadek Ayu; Ni Made Ayu Natih Widhiarini; Agung Rizky Fedora Febrawan (UHN IGB Sugriwa Denpasar, 2024)
Melukat is a ceremony to purify and cleanse the bad and dirty nature that exists in every human being. Melukat is a Balinese Hindu tradition that has been passed down from generation to generation and is still practiced today. In addition, Melukat is also said to be a